EFEKTIVITAS PERLINDUNGAN HUKUM TERHADAP KORBAN PEMERKOSAAN DALAM UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL (UU TPKS) - Suryantoro, Dwi Dasa (LPPM STAI Muhammadiyah Probolinggo, 2024)
With the enactment of the Sexual Violence Crime Law (UU TPKS) in 2022, the legal framework for addressing rape in Indonesia has undergone significant development. This legislation provides improved protection for rape victims, including victims' rights, legal safeguards, and measures for the prevention of sexual violence. The objective of this study is to evaluate the effectiveness of legal protection for rape victims under the UU TPKS. This research adopts a normative method with a conceptual and legislative approach. Secondary data, obtained indirectly through literature reviews, is used as the primary source for examining how the provisions of the UU TPKS are applied in relation to victims' rights, reporting mechanisms, and the obstacles hindering the implementation of legal protections for victims. The findings indicate that although the UU TPKS provides a robust legal foundation, its implementation faces numerous challenges, including a lack of understanding regarding victims' rights. Keywords: effectiveness, Rape, sexual violence,